Crystallization and sulfur SAD phasing of AggA, the major subunit of aggregative adherence fimbriae type I from the Escherichia coli strain that caused an outbreak of haemolytic‐uraemic syndrome in Germany. Issue 12 (1st December 2013) - Pakharukova, Natalia; Tuittila, Minna; Zavialov, Anton
<x xml:space="preserve">Abstract</x> The outbreak of Shiga toxin‐producing Escherichia coli O104:H4 infection in Germany in 2011 was associated with significant mortality and morbidity owing to the progressive development of haemolytic‐uraemic syndrome. The outbreak strain emerged recently as a result of horizontal transfer events leading to the acquisition of a number of virulence factors. Among them, aggregative adherence fimbriae type I (AAF/I) are considered to be particularly important since they are involved in the initial attachment of bacteria to the intestinal mucosa. Here, the crystallization and preliminary X‐ray diffraction analysis of the major subunit of AAF/I, AggA, are reported. Crystallization of recombinant donor‐strand complemented AggA was performed by the vapour‐diffusion method. The crystals diffracted to 1.55 Å resolution and belonged to the orthorhombic space group C2221, with unit‐cell parameters a = 77.83, b = 80.17, c = 91.42 Å. Despite a low sulfur content of the protein [0.57%(w/w)], sufficiently accurate initial phases were derived from a sulfur SAD experiment.